HUBUNGAN PEMBERIAN ANTIBIOTIK INTRAVENA DENGAN KEJADIAN FLEBITIS DI RSUD EMBUNG FATIMAH KOTA BATAM - Ronny Sutanto; Sitty Iqbalwanty (Universitas Batam, 2019)
One of the effects of handling an infectious case given intravenously is phlebitis caused by various things such as the tonicity of an antibiotic solution given including part of the nosocomial infection process. Phlebitis is inflammation of the venous wall due to intravenous fluid therapy, which is characterized by pain, redness, soft palpation, swelling, and warmth at the site of the puncture. The purpose of knowing the relationship of intravenous antibiotic drug injection with the incidence of phlebitis in Embung Fatimah Hospital in Batam City in 2018. This type of research is a case-control with a retrospective approach, conducted at the Embung Fatimah Regional General Hospital in Batam City in 2018. The population of all patients treated at the Embung Fatimah Regional General Hospital is infused and occurs during July - December 2018 as many as 3494 people. Sampling with a random sampling technique, a total of 97 people. Univariate results showed that intravenous antibiotic drug injections in the phlebitis group were 72 people (74.2%), 50 people were given antibiotics (69.4%). And intravenous antibiotic drug injections in the group of cases of non-phlebitis as many as 22 people (30.6%). Bivariate test results, square-test obtained p-value = 0.023 â‰¤ 0.05 and OR of 2.893. There is a significant relationship between intravenous antibiotic administration and phlebitis in Embung Fatimah District Hospital Batam City in 2018.